Analisys Of School Litaracy Movement at Kaiwatu State Elementry School - Tampombebu, Olivia Inriana; Lumbantobing, Winda Lidia; Pangemanan, Marsela Vanesa; Mangantibe, Amelia C. M; Elias, Sity Musdaliva (International Journal of Education, Information Technology, and Others, 2025)
This study aims to analyze the implementation of the School Literacy Movement at SD Inpres Kaiwatu Manado, identify factors and obstacles, and provide efforts to improve the effectiveness of the program. The research method used is qualitative with a descriptive approach. Data collection was conducted through in-depth interviews, observation, and documentation. The data analysis used in this study is model analysis, which begins with data reduction, data presentation, and conclusion drawing or verification. The results of this study show that the implementation of the School Literacy Movement at SD Inpres Kaiwatu has been carried out gradually and there are several challenges, such as limited infrastructure, lack of teacher training, and low parental participation. The main supporting factors are the commitment of the principal and the support of the school community. Efforts to improve include strengthening teacher capacity through continuous training, optimizing the role of the school library, and actively involving external stakeholders.